Nuestra luna - Lucas, Debra; Ramos, Gloria (Bloomington, Minn. : Red Brick Learning, 2006)
Presents information about the moon in a question and answer format, covering the phases of the moon, the nature of its surface, and human voyages there.
Includes index.
In Spanish.
Keywords: Astronomy -- Juvenile literature; Astronomy; Spanish language materials; Moon -- Juvenile literature; Moon; Spanish language materials; 2